2020
DOI: 10.47203/ijch.2020.v32i02.016
|View full text |Cite
|
Sign up to set email alerts
|

Ban on Sale of Loose Cigarettes: Awareness, Perceptions and Practices among Vendors and Smokers in Karnataka, India

Abstract: Background: The Government of Karnataka banned loose cigarettes sale effect from September 2017 and is punishable under Cigarettes and Other Tobacco Products Act (COTPA) with fine and imprisonment in case of violation. Aim & Objective: Study aims to assess awareness, perceptions and practices about ban among tobacco vendors and smokers. Methods and Material: Cross sectional survey was carried using pre-tested questionnaire to collect information regarding awareness about ban among vendors and smokers. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In a previous study, vendors’ reasons for selling loose cigarettes were demand from smokers, absence of health warnings, and benefits of selling more. 7 We found that the most common points of sale of LT were tea stalls, petty shops, pan shops, and bakeries. In earlier studies, they were general stores, followed by petty shops, bakeries, and street vendors.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…In a previous study, vendors’ reasons for selling loose cigarettes were demand from smokers, absence of health warnings, and benefits of selling more. 7 We found that the most common points of sale of LT were tea stalls, petty shops, pan shops, and bakeries. In earlier studies, they were general stores, followed by petty shops, bakeries, and street vendors.…”
Section: Discussionmentioning
confidence: 79%
“…Almost all surveyed smokers in this study were male. Previous studies have found that 1% of women purchased LT 7, 8 and that 43% of current female smokers bought loose cigarettes. 8 We found that 4% of tobacco vendors were female, whereas earlier studies did not report the gender of the vendors.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations